2020
DOI: 10.1371/journal.pone.0238412
|View full text |Cite
|
Sign up to set email alerts
|

Simulating phase transitions and control measures for network epidemics caused by infections with presymptomatic, asymptomatic, and symptomatic stages

Abstract: We investigate phase transitions associated with three control methods for epidemics on small world networks. Motivated by the behavior of SARS-CoV-2, we construct a theoretical SIR model of a virus that exhibits presymptomatic, asymptomatic, and symptomatic stages in two possible pathways. Using agent-based simulations on small world networks, we observe phase transitions for epidemic spread related to: 1) Global social distancing with a fixed probability of adherence. 2) Individually initiated social isolati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Simulation studies also suggest that there is a rapid phase transition from low to high prevalence of infection in populations as a function of compliance with social mitigation strategies such as mask usage. Mask usage below a threshold percentage of individuals results in widespread infection of the population 4 . Information on population compliance with mask usage is thus important to understanding the continuing dynamics of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies also suggest that there is a rapid phase transition from low to high prevalence of infection in populations as a function of compliance with social mitigation strategies such as mask usage. Mask usage below a threshold percentage of individuals results in widespread infection of the population 4 . Information on population compliance with mask usage is thus important to understanding the continuing dynamics of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, face mask use below a threshold percentage of people results in widespread infection of the population in the absence of other mitigation strategies. 5 However, the likelihood of an individual engaging in protective behaviors such as wearing a face mask may vary, with demographic differences among individuals. For example, a meta-analysis of protective behaviors in response to respiratory epidemics found significantly lower compliance among males than among females, 6 as have studies of face mask use during the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…These models represent a clear departure from the homogeneity assumptions of the traditional well-mixed compartment models and have already been used in the context of COVID-19 epidemic. Specifically, it has been shown that utilizing accurate social network models can provide better insights into the spread of the new coronavirus disease [51] , [52] , [53] , [54] , improve the forecast of the evolution of the epidemic [55] , [56] and help to design efficient strategies to control COVID-19 outbreaks [57] .…”
Section: Introductionmentioning
confidence: 99%